2020
DOI: 10.1016/j.msard.2020.102196
|View full text |Cite
|
Sign up to set email alerts
|

Are type 1 interferons treatment in Multiple Sclerosis as a potential therapy against COVID-19?

Abstract: Background: The Coronavirus (COVID-19), (Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)) has been spreading worldwide since its first identification in China. It has been speculated that patients with comorbidities and elderly patients could be at high risk for the pandemic reasoned respiratory insufficiency and death. At first, it was thought that the patients who use immunmodulator therapy could be even at higher risks of disease complications. However, it has been also speculated about that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 4 publications
0
22
0
1
Order By: Relevance
“…Significant differences in outcomes suggest that IFN might be an effective therapeutic agent for SARS‐CoV‐2 31 . The efficacy of IFN‐I against COVID‐19 was further supported in a case study 32 …”
Section: Clinical Studies Of Ifn‐i For Covid‐19mentioning
confidence: 80%
See 1 more Smart Citation
“…Significant differences in outcomes suggest that IFN might be an effective therapeutic agent for SARS‐CoV‐2 31 . The efficacy of IFN‐I against COVID‐19 was further supported in a case study 32 …”
Section: Clinical Studies Of Ifn‐i For Covid‐19mentioning
confidence: 80%
“…31 The efficacy of IFN-I against COVID-19 was further supported in a case study. 32 Nebulized IFN treatment for COVID-19…”
Section: Clinical Studies Of Ifn-i For Covid-19mentioning
confidence: 99%
“…The full-text screening of these studies led to the exclusion of 286 that did not meet the inclusion criteria. The remaining 26 studies were identified as eligible to be reviewed [ 6 , 7 , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis that certain DMT's may protect against severe complications of COVID-19, accounting for some of the favourable outcomes in reported cases, including anti-CD20 therapy (Ghajarzadeh et al, 2020;Giovannoni, 2020;Novi et al, 2020), Natalizumab (Aguirre et al, 2020) and interferon therapy (Gemcioglu et al, 2020) may require consideration in decision-making regarding DMT's as further real-world data emerges, but, based on the resources used for patient decision-making, is unlikely to have been pertinent to the relatively high proportion of patients who voiced a 'low' level of concern relating to their DMT use during the pandemic as low.…”
Section: Discussionmentioning
confidence: 99%